(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
In recent years, the problem of religious radicalism and the negative influence of social networks has been worrying the whole world. In this article, the essence and history of radicalism is explained and the outcomes that happened and still happening as a result of it also has been analysed. It has been revealed that social media is being used as a weapon in the escalation of radicalism. As a result of this, it will spread rapidly across the world and particularly young generation will be negatively affected by it.